Consumer segmentation based on usage of sales channels in the German wine market. Issue 1 (2014) - Gergely Szolnoki; Dieter Hoffmann
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this study is to test the segmentation based on the usage of sales channels and to compare the segments with each other in terms of socio‐demographic and behavioural characteristics. Design/methodology/approach – This study was conducted using representative data collected in Germany through a face‐to‐face interview. 2, 000 German consumers answered questions towards the usage of different sales channels when purchasing wine as well as socio‐demographic and other behavioural questions. A hierarchical cluster analysis was run, to classify the respondents into segments. Findings – The results illustrate the usefulness of this kind of segmentation and show significant differences between the six consumer groups: discount‐customers, food‐retail‐customers, supermarket‐customers, cellar‐door‐customers, wine‐store‐customers and multichannel‐customers. These segments differ in their socio‐demographic as well as in their behavioural structure. Furthermore, the six segments could be split into two groups depending on their average purchase value: a basic group and a premium group. Practical implications – This segmentation provides an analysing tool for the German retailers, which is able to identify the loyal and potential consumers of the different sales channels. Originality/value – This segmentation was conducted using the purchase activity of German consumers in different sales channels. This segmentation approach has been never used to identify, describe and classify wine consumers.